2014
DOI: 10.1136/bmjopen-2013-004250
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study to compare two blood collection methods: direct venous puncture and peripheral venous catheter

Abstract: ObjectivesTo demonstrate the equivalence between blood collection methods using direct venous puncture (DVP) and a peripheral venous catheter or cannula (PVC).Design and settingA cross-sectional study of simple crossover design with within-subject measures carried out between October 2011 and May 2012 at a regional hospital in Spain.Participants272 patients aged 18 or older hospitalised or admitted to the short-stay unit (SSU) who required laboratory testing and PVC to administer saline solution, intravenous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 27 publications
0
36
0
Order By: Relevance
“…While all blood samples were obtained from catheters, we do not anticipate that this sampling method affected the measured Aβ concentrations compared to venous puncture sampling. 32 Additionally, we do not believe that central venous catheterization significantly altered the Aβ measurements by disrupting the BBB as the blood was collected upstream from the tip of the catheter.…”
Section: Discussionmentioning
confidence: 97%
“…While all blood samples were obtained from catheters, we do not anticipate that this sampling method affected the measured Aβ concentrations compared to venous puncture sampling. 32 Additionally, we do not believe that central venous catheterization significantly altered the Aβ measurements by disrupting the BBB as the blood was collected upstream from the tip of the catheter.…”
Section: Discussionmentioning
confidence: 97%
“…This approach was favored to maintain mother’s flexibility in contact with their babies during the experimental setup. Although venipuncture induces a pain stimulus and therefore may result in acute effects on circulating stress hormones, recent studies indicate that blood sampling for most laboratory tests using either direct venous puncture or peripheral venous catheter reveal comparable results (Ortells-Abuye et al, 2014). For cortisol, resting time prior to the first blood sampling may take a minimum of 30 min, which should be ameliorated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sample sizes varied significantly with the number of patients being between 17 and 54,531 and data collection periods varying between 19 days and 12 months. A few studies excluded patients who were unstable or with multiple comorbidities (Hambleton et al, ; Himberger & Himberger, ; Ortells‐Abuye et al, ; Seemann & Reinhardt, ) and one study only included healthy volunteers (Zlotowski et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…One study (Hambleton et al, ) summarized the results as all parameters were within the laboratory's accepted error except for venous blood gases. Similarly, another study (Ortells‐Abuye et al, ) also summarized blood results, which could be considered equivalent with the exception of venous blood gases. In contrast, one study (Zlotowski et al, ) found blood samples for potassium, bicarbonate and glucose were not clinically equivalent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation